2023
DOI: 10.1186/s40537-023-00692-w
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of deep learning techniques for DoS attacks detection in wireless sensor network

Abstract: Wireless sensor networks (WSNs) are increasingly being used for data monitoring and collection purposes. Typically, they consist of a large number of sensor nodes that are used remotely to collect data about the activities and conditions of a particular area, for example, temperature, pressure, motion. Each sensor node is usually small, inexpensive, and relatively easy to deploy compared to other sensing methods. For this reason, WSNs are used in a wide range of applications and industries. However, WSNs are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The model is noted for its reduced processing overhead, a validated solution on resource constraint hardware and achieved an accuracy of 0.9888 -0.9987 among the different datasets used to train the model. This study is supported by [10] in their study which sought to develop efficient deep learning-based algorithm for the detection of DDoS attacks in wireless sensor networks, reporting CNN as the best classifier which outperformed the other algorithms with an accuracy rate of 98.79%. The other algorithms, outperformed by the CNN classifier were DNN, RNN and CNN-RNN, trained on the WSN-DS.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…The model is noted for its reduced processing overhead, a validated solution on resource constraint hardware and achieved an accuracy of 0.9888 -0.9987 among the different datasets used to train the model. This study is supported by [10] in their study which sought to develop efficient deep learning-based algorithm for the detection of DDoS attacks in wireless sensor networks, reporting CNN as the best classifier which outperformed the other algorithms with an accuracy rate of 98.79%. The other algorithms, outperformed by the CNN classifier were DNN, RNN and CNN-RNN, trained on the WSN-DS.…”
Section: Introductionmentioning
confidence: 74%
“…The deep neural networks, with their capability to learn complex patterns in data makes them very effective models to deploy. In this review, [10] proposed model is one such model which showed a good classification accuracy with CNN classifier. Nonetheless, the hybrid model deployed in that study could yield an optimal outcome if feature selection is done for dimensionality reduction on the dataset coupled with extensive hyperparameter tuning.…”
Section: Again Pandian Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the specific characteristics of node distribution and data transmission in sensor networks, attackers primarily launch attacks from two directions ( Yousefpoor et al, 2021 ; Salmi & Oughdir, 2023 ; Cao et al, 2022 ): Eavesdropping attacks are a prevalent form of attack in wireless sensor networks. In WSNs, where data transmission occurs wirelessly between nodes, attackers can intercept and eavesdrop on the communication channel.…”
Section: Preliminary Workmentioning
confidence: 99%